High-fat diet exacerbates SIV pathogenesis and accelerates disease progression - He, Tianyu (J Clin Invest, 2019)
Consuming a high-fat diet (HFD) is a risk factor for obesity and diabetes; both of these diseases are also associated with systemic inflammation, similar to HIV infection. A HFD induces intestinal dysbiosis and impairs liver function and coagulation, with a potential negative impact on HIV/SIV pathogenesis. We administered a HFD rich in saturated fats and cholesterol to nonpathogenic (African green monkeys) and pathogenic (pigtailed macaques) SIV hosts. The HFD had a negative impact on SIV disease progression in both species. Thus, increased cell-associated SIV DNA and RNA occurred in the HFD-receiving nonhuman primates, indicating a potential reservoir expansion. The HFD induced prominent immune cell infiltration in the adipose tissue, an important SIV reservoir, and heightened systemic immune activation and inflammation, altering the intestinal immune environment and triggering gut damage and microbial translocation. Furthermore, HFD altered lipid metabolism and HDL oxidation and also induced liver steatosis and fibrosis. These metabolic disturbances triggered incipient atherosclerosis and heightened cardiovascular risk in the SIV-infected HFD-receiving nonhuman primates. Our study demonstrates that dietary intake has a discernable impact on the natural history of HIV/SIV infections and suggests that dietary changes can be used as adjuvant approaches for HIV-infected subjects, to reduce inflammation and the risk of non-AIDS comorbidities and possibly other infectious diseases.